Mycoplasma and other Intracellular Bacterial Infections in Rheumatic Diseases: Comorbid Condition or Cause? - Garth L Nicolson (Open Journal of Tropical Medicine - Peertechz Publications, 2017)
Although the causes of rheumatic diseases have remained relatively unknown, systemic intracellular bacterial infections are commonly found in rheumatic disease patients [1-4].Because of this, certain infections have been confused with comorbid conditions.Often patients with rheumatic diseases have co-morbidities, and some authors have concluded that this can include chronic morbidity and mortality in patients with rheumatic diseases,and, consequently, early diagnosis and treatment of infection is critical to the successful medical management of these patients" [5].